Polydrug use at raves by a Western Australian sample - Boys, A.; Lenton, Simon; Norcross, K. (1997)
This study aimed to quantify the patterns of drug use among a group of participants in the rave scene in Perth, Western Australia.Interviews were conducted with 83 people who had recently been to a "rave". The study incorporated a semi-structures qualitative interview and a structured quantitative questionnaire. This paper reports on the quantitative data collected concerning patterns of drug use in association with the last rave attended. Use of "dance drugs" (ecstasy, amphetamines or LSD) was reported by 86.8% of the 76 respondents who had used at least one other drug in association with their last rave. Nearly 80% of these had also used at least one other drug on this occasion (mean number used=2.4). Cannabis and inhalants were the drugs most commonly combined with the "dance drugs", several respondents used more than one "dance drug" concurrently and 16.7% had used alcohol. It seems that a significant proportion of those using "dance drugs" in association with raves and dance parties are mixing these drugs with other substances despite harm reduction to the contrary. The need for more research in this area is discussed.